Faktor Yang Berhubungan Dengan Keluhan Low Back Pain Pada Pegawai Dinas PU Kota Makassar - Tanri Abeng, Tenri Diah; Adhinda Putri Pratiwi (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2023)
Ergonomics as a science that seeks to harmonize between human factors, work factors and environmental factors. One of the ergonomic problems that occur is complaints of low back pain in workers. In 2022, most workers at the Makassar City Public Works Office will complain of low back pain due to the large number of activities carried out so that workers experience lower back pain when they finish work. So the purpose of this study was to find out the factors associated with complaints of low back pain in workers at the Public Works Office of Makassar City. The type of research used is an analytic survey with a cross sectional design. The population in this study were 116 employees and the sample for this study was the entire population of 116 people. Respondent data collection using a questionnaire. Data analysis using the Chi-Square Test. The results of this study showed that there was a relationship between age (p=0.005) and complaints of low back pain, there was a relationship between length of work (p=0.026) and complaints of low back pain, and there was a relationship between posture (p=0.008) and complaints of low back pain. The conclusion in this study is that all variables in the study have a relationship with the occurrence of low back pain complaints in workers at the Public Works Office of Makassar City.